Food cue-induced craving in individuals with bulimia nervosa and binge-eating disorder - Meule, Adrian; Küppers, Carolyn; Harms, Louisa; Friederich, Hans-Christoph; Schmidt, Ulrike; Blechert, Jens; Brockmeyer, Timo (PLOS ONE, 2018)
Individuals with bulimia nervosa (BN) or binge-eating disorder (BED) experience more frequent and intense food cravings than individuals without binge eating. However, it is currently unclear whether they also show larger food cue-induced increases in craving (i.e., food cue reactivity) than those without binge eating, as suggested by conditioning theories of binge eating. A group of individuals with BN or BED (binge-eating group, n = 27) and a group of individuals with low trait food craving scores and without binge eating (control group, n = 19) reported their current food craving before and after a food cue exposure. Although food craving intensity significantly increased in both groups, this increase was significantly stronger in the binge-eating group than in the control group. This result is in line with conditioning models of binge eating that propose that food cues are conditioned stimuli that elicit a conditioned response (e.g., food craving) and that this association is stronger in individuals with binge eating. As food craving increased in individuals with low trait food craving scores as well-although to a lesser extent-previous null results might be explained by methodological considerations such as not screening control participants for trait food craving.